췌장지방증에서 대사성질환의 위험 요인에 관한 연구 - 조진영(Jin Young Cho); 예수영(Soo Young Ye); 김동현(Dong Hyun Kim) (방사선기술과학, 2016)
The body of the fat tissue increased in obese represented by risk factors such as cardiovascular diseases, diabetes, metabolic disease and dyslipidemia. Such metabolic diseases and the like of the cardiovascular and cerebrovascular disease, hypertension, dyslipidemia, increase in the adipose tissue of the pancreas is known to be a risk factor of these diseases. Study on the diagnosis and treatment of pancreatic cancer was conducted actively, case studies on pancreatic steatosis is not much. In this study, divided into a control group diagnosed with pancreatic steatosis as a result of ultrasonography to evaluation the physical characteristics and serologic tests and blood pressure and arterial stiffness. The control group and the test pancreas steatosis age and waist circumference, body mass index, total cholesterol, HDL cholesterol, LDL cholesterol, and systolic and diastolic blood pressure, fasting blood glucose, arterial elasticity is higher in pancreatic steatosis. And the lower ankle brachial stenosis and HDL-cholesterol were lower than the normal control group, so the pancreatic steatosis harmful to blood vessels.(P <0.05). The difference between the control group and it was confirmed that the pancreatic jibanggun statistically significant. In conclusion, pancreatic steatosis at abdominal ultrasound can predict the risk of metabolic diseases, and there was a correlation with cardiovascular disease. 인체의 지방조직이 증가하여 비만해지면 심혈관계 질환, 당뇨병, 대사성질환과 이상지질혈증 등의 위험인자로 나타난다. 이러한 대사성질환에는 심혈관 및 뇌혈관질환, 고혈압, 고지혈증 등이 있고, 췌장의 지방조직 증가는 이러한 질환의 위험요인으로 알려져 있다. 그리고 췌장암에 대한 진단과 치료에 대한 연구는 활발히 이루어졌으나, 췌장지방증에 관한 연구 사례는 많지 않다. 본 연구에서는 초음파 검사의 결과로 진단된 췌장지방군과 정상대조군으로 나누어 신체 특성과 혈청학적 검사와 혈압 및 동맥경화도검사를 평가하였다. 정상대조군과 췌장지방군 사이에서 연령이나 허리둘레, 체질량 지수, 총 콜레스테롤, HDL 콜레스테롤과 LDL 콜레스테롤, 수축기와 이완기혈압, 공복혈당, 대동맥 맥파전파속도는 췌장지방군에서 높게 나타났다. 그리고 족관절상완협착비와 HDL-콜레스테롤은 낮을수록 혈관에 유해하므로 췌장지방군이 정상대조군보다 낮게 나타났다(p < 0.05). 정상대조군과 췌장지방군의 차이가 통계적으로 유의함을 확인할 수 있었다. 결론적으로 복부초음파 검사에서 췌장지방증은 대사성 질환의 위험을 예측할 수 있으며 심혈관계 질환과 연관성이 있었다.